(untitled) (Research, Society and Development, 2025)
Experimental models of thiamine deficiency (TD) have primarily focused on male rodents, meaning that the effects of TD in females and the pathogenesis associated with neurological disorders remain unknown. This article aimed to present an investigation on the effects of TD with amprolium in female mice, evaluating metabolic and behavioral effects, as well as the modulation of ERK1/2 phosphorylation in the cerebral cortex and thalamus. Furthermore, we used the antioxidant Trolox and anti-inflammatory agent dimethyl sulfoxide to investigate the role of oxidative stress and neuroinflammation in this process. The animals were exposed to a thiamine-deficient diet with the additional administration of amprolium (60 mg/kg) for 20 days. After treatment, we observed a reduction in food consumption and animal body weight, with a decrease in motor coordination and exploratory activity, and, in parallel, an increase in the phosphorylation of ERK1/2, both in the cerebral cortex and thalamus in deficient animals. Deficient animals that received Trolox or dimethyl sulfoxide presented with attenuation of these effects, with the maintenance of motor coordination and total blockage of ERK1/2 activation. The results showed that female mice could be used as a valid TD model, compatible with other methods, showing important neurological changes. This study showed that in females, TD also involves mechanisms of oxidative stress and inflammation, responds positively, and can be used as a model animal.